Stres proza życia – analiza wybranych grup zawodowych w perspektywie zagrażajacych bodzców stresowych - Judzińska, Aneta (Kultura-Społeczeństwo-Edukacja, 2013)
Article examines the occurrence of professional stress among academic teachers (postgraduate students), doctors and policemen particularly exposed to intensive in uence of stressful impulses for social character of the functions they perform. Basing on the literature of object, author enriches the analysis with his own ndings. In rst instance he de nes the notion of stressors and then he tries to nd and make them up in the form of specific threats, adequate for each of the above mentioned professional groups. His analysis is extended by the aspect of professional transformations taking into consideration their social-cultural conditions. Thanks to it the author shows the existence of relationship not only between the age of respondents and susceptibility on stress but he underlines as well how important place in human’s needs hierarchy takes the professional job. Frustration, fear, tension and anxiety destructively in uence the psychical form of an individual e ecting in negative consequence de ned by the hereby article as a professional burnout.